MYTHOLOGY CONSTRUCTIONS IN COSMETIC ADVERTISEMENTS AND CONSUMERS’ COGNITION - Andi Muhammad Irawan (Asian Journal of Innovation and Entrepreneurship, 2012)
This article discusses about mythology constructions in cosmetic advertisements which influence the consumers’ cognition. Semiology, particularly Barthes’ mythology, is used as an analysis to reveal the the process of imposition or appropriation of the cultural-connotative meaning into the cosmetic advertisements through linguistic and non-linguistic signs. This article is based on the research which was conducted in 2010 as the part of Roland Barthes’ Mythology study which is applied to cosmetic advertisements in Television. The constructed Myth through linguistic and non-linguistic signs, namely myth of “white skin”, can persuade the consumers’ cognition to buy the cosmetic products. The result of this research shows that the connotative meaning imposed to the signs can trigger the consumers to buy the products. This evidence can be identified through the consumers’ perception in interview.Keywords: mythology construction, semiology, connotative meaning, linguistic and non-linguistic signs, cosmetic advertisements, consumers’ cognition